HLA-G/ILTs Targeted Solid Cancer Immunotherapy: Opportunities and Challenges - Lin, Aifen; Yan, Wei-Hua (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) have became a promising immunotherapy for cancers. Human leukocyte antigen-G (HLA-G), a neoantigen, its biological functions and clinical relevance have been extensively investigated in malignancies, and early clinical trials with “anti-HLA-G strategy” are being launched for advance solid cancer immunotherapy. The mechanisms of HLA-G as a new ICI is that HLA-G can bind immune cell bearing inhibitory receptors, the immunoglobulin-like transcript (ILT)-2 and ILT-4. HLA-G/ILT-2/-4 (HLA-G/ILTs) signaling can drive comprehensive immune suppression, promote tumor growth and disease progression. Though clinical benefits could be expected with application of HLA-G antibodies to blockade the HLA-G/ILTs signaling in solid cancer immunotherapy, major challenges with the diversity of HLA-G isoforms, HLA-G/ILTs binding specificity, intra- and inter-tumor heterogeneity of HLA-G, lack of isoform-specific antibodies and validated assay protocols, which could dramatically affects the clinical efficacy. Clinical benefits of HLA-G-targeted solid cancer immuotherapy may be fluctuated or even premautre unless major challenges are addressed.